The traditional lunch pattern is inversely correlated with body mass index in a population-based study in Brazil - Roberta de Oliveira Santos; Diva Aliete dos Santos Vieira; Andreia Alexandra Machado Miranda; Regina Mara Fisberg; Dirce Maria Marchioni; Valéria Troncoso Baltar (BMC, 2017)
Abstract Background The association of obesity and dietary patterns has been well documented in scientific literature; however, information on the impact of meal patterns on obesity is scarce. The objective of this study was to investigate the association of adherence to lunch patterns and body mass index (BMI) in a representative sample of individuals aged 20 years or older in Sao Paulo. Methods Data for 933 participants were retrieved from the Health Survey of São Paulo (ISA-Capital 2008), a cross-sectional population-based survey. The usual dietary intake of individuals with at least one 24-h recall was estimated by the Multiple Source Method. The definition of lunch was self-reported by the participant. Five lunch patterns were derived from twenty-two food groups by exploratory factor analysis: Traditional, Western, Sweetened juice, Salad, and Meats. To estimate the effect of lunch patterns on BMI, we used a generalized linear model with link identity and inverse Gaussian distribution. Analyses were adjusted by age, gender, household income per capita, physical activity levels, smoking status, alcohol consumption, total energy intake, and misreporting status. Results The greater adherence to the traditional pattern at the lunch meal was associated with lower BMI, only in insufficiently active individuals (ß = −0.78; 95% CI -1.57; −0.02). Conclusions The traditional Brazilian lunch pattern might protect the insufficiently active individuals against obesity.